Point of Care Haemoglobin Estimation - Swaminathan, Sumathi; Thomas, Tinku; Bose, Beena; Kurpad, Anura V (Indian Journal of Community Health, 2018)
The prevalence of anemia in India is still unacceptably high at 53.1 % in non-pregnant women, 50.3% in pregnant women, 58.4% in children 6 months and 22.7% in adult men(1) and remains a major public health problem. For screening, tracking as well as monitoring the progress of anemia in both in primary and community health care for public health programs, hemoglobin needs to be estimated accurately.